Transradial Approach for Diagnostic Selective Cerebral Angiography: Results of a Consecutive Series of 166 Cases - Matsumoto, Yasushi; Hongo, Kazuhiro; Toriyama, Toshihide; Nagashima, Hisashi; Kobayashi, Shigeaki (American Journal of Neuroradiology, 2001)
BACKGROUND AND PURPOSE: Diagnostic selective cerebral angiography is commonly performed via transfemoral and transbrachial approaches. With these approaches, however, patients occasionally suffer serious complications. The purpose of this study was to evaluate the feasibility, efficacy, and safety of a transradial approach as an alternative to the transfemoral and transbrachial approaches.METHODS: Between October 1998 and September 1999, transradial cerebral angiography was performed in 166 consecutive patients in a single center as a diagnostic procedure. Before the procedure, we confirmed the collateral blood supply to the hand from the ulnar artery using a modified Allen test. Regular catheterization techniques were practiced using our newly designed 120-cm-long 4F catheter. In 42 patients, anticoagulant and/or antiplatelet therapy was given perioperatively.RESULTS: Twelve of the 166 patients proved to be poor candidates for the transradial approach, owing to restlessness (n = 9), lack of collateral blood supply via the ulnar artery (n = 2), and brachial artery stenosis (n = 1). The radial artery was successfully punctured and cannulated in the remaining 154 patients. Selective catheterization of the intended vessels was obtained in all carotid and vertebral angiographic procedures with no major vascular complications.CONCLUSION: Compared with transfemoral and transbrachial approaches, the transradial approach is a less invasive and safer technique for selective cerebral angiography and may warrant consideration as a standard procedure. Anticoagulant or antiplatelet therapy need not be discontinued for this method.